Use of coconut oil in the production of cosmetics: a bibliographic review (Research, Society and Development, 2020)
Objective: The present work aims to analyze the use of coconut oil (Cocos nucifera L) in cosmetics. Methodology: This is a bibliographic review, produced from the search for scientific publications, listed in the following databases: PubMed Central - PMC, Scientific Electronic Library Online - SCIELO, EBSCOhost Research Platform - EBSCO. It was carried out in advanced research, with the descriptors: cosmetics and coconut oil, using the terms cosmetics and Coconut Oil, between August and October 2020. Results: Eleven articles were found, it was agreed with what was suggested throughout the selected articles, that coconut oil shows itself as a good alternative in the use in cosmetic products due to its organoleptic physico-chemical characteristics. Conclusion: the use of coconut in the manufacture of cosmetic products, becomes a viable option, as it has a highly hydrating property effective in skin care, due to its high concentration of lauric acid, a type of fatty acid with antiseptic properties, efficient in combating microorganisms that cause skin diseases.